Secondary Metabolite Production in Callus Cultures of Stevia rebaudiana Bertoni - Janarthanam, B; Gopalakrishnan, M; Sekar, T (Bangladesh Journal of Scientific and Industrial Research, 2010)
Stevia rebaudiana is and an important non-caloric sweetening herb contains diterpene glycosides need to be explored for its commercialization. The evolving commercial importance of secondary metabolites in recent years has resulted in a great demand in the Pharma industry. Callus cultures were established from nodal and leaf explants. Leaf explants showed better callus initiation than nodal explants. Maximum callus biomass was observed in MS medium supplemented with 2, 4-D 1.0 mg/l. Further screening of callus culture was carried out on Murashige and Skoog (MS) medium with different concentration and combinations of 2, 4-D, NAA, IAA, IBA, BA and KN individually and in combinations. Remarkable callus biomass of 11.6 g/l dry weight (182.3 g/l fresh weight) was observed in MS media containing 0.5 mg/l 2, 4-D, 0.5 mg/l NAA and 1.0 mg/l KN. The harvested cell biomass was subjected to extraction of active principles. In this study, cell biomass extracts were compared with extracts from leaves of mother plants of Stevia rebaudiana. HPLC analysis of these extracts showed that the main components of the active principles namely Stevioside were present in sufficiently large amounts in the undifferentiated cultured cells. Keywords: In vitro culture; Biomass; Stevia rebaudiana; Stevioside DOI: 10.3329/bjsir.v45i3.6532 Bangladesh J. Sci. Ind. Res. 45(3), 243-248, 2010